'Uncertainty is the only certainty': how pragmatic sociology provides a useful theoretical framework for researching the third sector during COVID-19. (1st March 2021) - Petzinger, Janis; Jung, Tobias; Orr, Kevin
Abstract : This research note argues that pragmatic sociology is a useful theoretical framework when researching the third sector during the uncertain times of COVID-19 and beyond. It begins by introducing pragmatic sociology, which describes how actors express their values through the 'orders of worth' framework, and then how they justify their practices during moments of conflict, through the process of 'tests'. This ultimately employs complex and fragile moments in history to uncover meaning making and, by extension, individual and organisational practice. This article then demonstrates useful research questions that pragmatic sociology can offer for the third sector during this uncertain time and how this theory's utility can be applied even after the pandemic, due to its embracement of organisational dynamism, nuance and a fresh approach to power relationships.